2018
DOI: 10.1016/j.pscychresns.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal effects of cognitive behavioral therapy for depression on the neural correlates of emotion regulation

Abstract: Cognitive behavioral therapy (CBT) is effective for a substantial minority of patients suffering from major depressive disorder (MDD), but its mechanism of action at the neural level is not known. As core techniques of CBT seek to enhance emotion regulation, we scanned 31 MDD participants prior to 14 sessions of CBT using functional magnetic resonance imaging (fMRI) and a task in which participants engaged in a voluntary emotion regulation strategy while recalling negative autobiographical memories. Eighteen h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 60 publications
1
23
0
Order By: Relevance
“…For instance, there is some evidences that MDD patients are able to efficiently use reappraisal, when they "explicitly trained to do so" (Ebneabbasi, 2020;Liu and Thompson, 2017). Several neuroimaging studies also reported the intact neural underpinning of reappraisal in MDD (Davis, et al, 2018;Doré, et al, 2018;Loeffler, et al, 2019;Rubin-Falcone, et al, 2020;Rubin-Falcone, et al, 2018). Importantly, when non-significant results are published, they are not usually entered in ALE meta-analyses.…”
Section: Questionable Research Practices and Publication Biasmentioning
confidence: 99%
“…For instance, there is some evidences that MDD patients are able to efficiently use reappraisal, when they "explicitly trained to do so" (Ebneabbasi, 2020;Liu and Thompson, 2017). Several neuroimaging studies also reported the intact neural underpinning of reappraisal in MDD (Davis, et al, 2018;Doré, et al, 2018;Loeffler, et al, 2019;Rubin-Falcone, et al, 2020;Rubin-Falcone, et al, 2018). Importantly, when non-significant results are published, they are not usually entered in ALE meta-analyses.…”
Section: Questionable Research Practices and Publication Biasmentioning
confidence: 99%
“…Some athletes fail to show their true performance due to anxiety and stress or being monitored by the spectators and the media. In fact, in addition to the daily stresses, the athletes would be under special stress of the competition field, which needs psychological interventions (12). McGuir and Storch (13) stated that stress and anxiety of competition and the unpleasant feelings after losing a game or the stresses before, after, or during a game are all among the reasons that make it necessary for athletes to receive professional services.…”
Section: Introductionmentioning
confidence: 99%
“…In major depression, precentral cortical activation has been observed in response to working memory load (Walsh et al, 2007) as well as to negative emotional pictures and facial processing of sad, angry (Frodl et al, 2009;Fu et al, 2004) and fearful (Arnone et al, 2012) expressions in major depression (meta-analysis: (Zhao et al, 2014). Longitudinal studies have further demonstrated that emotion-regulation dependent reductions in the precentral gyrus after treatment was associated with improved treatment outcome (Rubin-Falcone et al, 2018). A key mechanism in cognitive behavioral therapy is cognitive change, whereby the treatment improves the maladaptive cognitions that are characteristic of major depression (Beck, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Increases in anterior cingulate activity following psychotherapy has been associated with improvement in rumination (Yoshimura et al, 2013) and treatment response (Goldapple et al, 2004), although improvements in depression severity was also associated with decreases in anterior cingulate following long-term psychodynamic therapy (Buchheim et al, 2012), perhaps indicative of specificity of effects of the different forms of psychological therapies. Longitudinal neuroimaging studies have further revealed reductions in bilateral cerebellum that were correlated with improvement in depression (Rubin-Falcone et al, 2018). Although the cerebellum is usually associated with motor control, language and attention, cerebellar engagement has also been noted during sad mood induction by musical pieces (Mitterschiffthaler et al, 2007).…”
Section: Discussionmentioning
confidence: 99%